2018
DOI: 10.1155/2018/7935396
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Vitamin E and Metallothionein on the Antioxidant Capacities of Cadmium-Damaged Liver in Grass Carp Ctenopharyngodon idellus

Abstract: Cadmium (Cd) causes a broad spectrum of toxicological effects to animals. Aquatic animals were more likely to accumulate Cd than terrestrial animals because of the living environment. Clearance of Cd in aquatic animals has become an important part of aquatic food safety. The present study was focused on the oxidative damage induced by Cd in the liver of grass carp Ctenopharyngodon idellus and the protective effect of vitamin E (VE) and metallothionein (MT). Grass carp were divided into four groups: the control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Perhaps this also applies to T 2 which in both 10 th and 12 th weeks of exposure are significantly higher than other treatments; and the highest mean value of AST produced in the liver (150.63±0.18nM/mg) was also obtained in T 2 at the end of the 4 th week of exposure probably because the enzymes produced in the higher concentrations have been put to greater use than in lower concentrations. This is in conformity with the findings of Feng et al [16] who reported that, the ameliorative role of vitamins was evident when Vitamin E and metallothionein treatments protected against Cd-induced damage of liver in grass carp by decreasing AST and ALT content, repairing organelles, and maintained the antioxidant system by elevating CAT, SOD, and GSH-Px activity and regulating related mRNA transcript expression. Furthermore, T 3 and T 4 mean values in the kidneys of the samples at the end of the 2 nd and 6 th weeks of exposure, respectively are significantly higher than other treatments due to the probable need for up-regulations of the body's defence system in tackling the effects of the toxicant especially at the inception.…”
Section: Ast Production Levels In C Gariepinus Exposed To Sub-lethal Concentrations Of Cd Toxicant and Supplemented With Vitamin Esupporting
confidence: 93%
See 1 more Smart Citation
“…Perhaps this also applies to T 2 which in both 10 th and 12 th weeks of exposure are significantly higher than other treatments; and the highest mean value of AST produced in the liver (150.63±0.18nM/mg) was also obtained in T 2 at the end of the 4 th week of exposure probably because the enzymes produced in the higher concentrations have been put to greater use than in lower concentrations. This is in conformity with the findings of Feng et al [16] who reported that, the ameliorative role of vitamins was evident when Vitamin E and metallothionein treatments protected against Cd-induced damage of liver in grass carp by decreasing AST and ALT content, repairing organelles, and maintained the antioxidant system by elevating CAT, SOD, and GSH-Px activity and regulating related mRNA transcript expression. Furthermore, T 3 and T 4 mean values in the kidneys of the samples at the end of the 2 nd and 6 th weeks of exposure, respectively are significantly higher than other treatments due to the probable need for up-regulations of the body's defence system in tackling the effects of the toxicant especially at the inception.…”
Section: Ast Production Levels In C Gariepinus Exposed To Sub-lethal Concentrations Of Cd Toxicant and Supplemented With Vitamin Esupporting
confidence: 93%
“…The results obtained also indicated that the tissue injury in toxicated fish recovered when they were fed dietary ascorbic acid because the AST and ALT activities in fish exposed to the lower or higher dose of ochratoxin + vitamin C became similar to those of control fish. The ameliorative role of vitamins was evident when Vitamin E and metallothionein treatments protected against Cd-induced damage of liver in grass carp by decreasing AST and ALT content, repairing organelles, and maintained the antioxidant system by elevating CAT, SOD, and GSH-Px activity and regulating related mRNA transcript expression [16]. This research therefore, addresses the effects of Cd toxicant on AST production levels and how such effects can be attenuated to certain extent by administration of vitamin supplements.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, previous studies proved the hepatorenal protective effect of Vit E against abamectin [15] and fipronil [17] toxicities. Vitamin E is well known to be potent natural antioxidant; it has important functional properties in membranes lipoprotein, it exerted an efficient antioxidant role by neutralization of ROS and up-regulation of antioxidant enzymes and reduction in lipid peroxidation [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on animal models exposed to Cd have shown a beneficial effect of vitamin E supplementation on the gastrointestinal tract, which was associated with a reduction in the severity of oxidative stress in the liver [4][5][6][7][8][9][10]. In studies on rats exposed to Cd, vitamin E also contributed to an increase in intracellular liver calcium and reversal of morphological changes in this organ [4], caused a reduction in histological changes in the liver [11], and in addition, an increase in animal body weight and liver weight [5], as well as a reduction in histopathological [5,7], and morphological changes of liver cells [12], and in Cd accumulation [5,6], and addition an increase in vitamin E concentration in the liver [5,13] were observed. In a study on fish exposed to Cd, a positive effect of vitamin E on liver function parameters was also observed -reduction of alanine aminotransferase (ALT) activity in the blood [14].…”
Section: Vitamin Ementioning
confidence: 99%